Nature and efficacy of interventions addressing eating psychopathology in athletes: A systematic review of randomised and nonrandomised trials. (8th January 2020) - Sandgren, Sebastian S.; Haycraft, Emma; Plateau, Carolyn R.
Abstract: Objective: This systematic review aimed to evaluate the nature of interventions addressing eating psychopathology in athletes, identify the characteristics of successful interventions, and review the efficacy of interventions at reducing or preventing eating psychopathology. Method: SPORTDiscus, MEDLINE, and PsycINFO were searched to identify studies addressing eating psychopathology in athletes, which included an outcome measure of disordered eating. Results: Seventeen studies (11 randomised controlled trials, six nonrandomised trials) reporting data on 13 interventions were included. The methodological quality was observed to be generally low. All interventions (11 implemented in North America) were delivered face to face in groups with variable duration and intensity. Thirteen studies reported significant reductions in athletes' eating psychopathology following the intervention, with seven reporting sustained effects (small to moderate). Successful interventions were characterised by higher intervention dosage, higher retention, and incorporated a focus on self‐esteem and self‐efficacy. Conclusion: The complex nature of interventions, combined with a lack of evaluation data and poor methodological quality, limits the scaling and refinement of many interventions. Future research should explore other modes of delivery, collect evaluation data, and adhere to clearer study reporting. Doing this will consequently improve the development and delivery of effective eating psychopathology interventions offered to athletes more widely.